1
$\begingroup$

Let $$A= \left[\begin{matrix} a & b & c \\ p & q & r \\ x & y & z \\ \end{matrix} \right]$$ be an idempotent matrix with rank 2. Then the rank of $$B= \left[ \begin{matrix} a-1 & b & c \\ p & q-1 & r \\ x & y & z-1 \\ \end{matrix} \right]$$ is?

Since the matrix $B$ can be written as $B=A-I$. And one of property of idempotent matrix says that the trace of an idempotent matrix = rank of matrix. this implies that $a+q+z=2$? and therefore, rank of $(a-1)+(q-1)+(z-1)=2-3=-1$? But how rank cannot be negative. Where am I going wrong?

$\endgroup$
  • $\begingroup$ We have $B^2=(A-I)(A-I)=A^2-2A+I=A-2A+I=I-A=-B$, so $B$ is not idempotent. $\endgroup$ – Dietrich Burde Sep 12 '16 at 19:43
1
$\begingroup$

Since $A$ is idempotent, then $A^2 = A$. This means that:

$$A^2 - A = 0 \Rightarrow A(A-I) = 0 \Rightarrow AB = 0.$$

For the Sylvester’s rank inequality, we have that:

$$\text{rank}(A) + \text{rank}(B) - n \leq \text{rank}(AB) \Rightarrow \\ 2 + \text{rank}(B) - 3 \leq 0 \Rightarrow\\ \text{rank}(B) \leq 1,$$

where $n=3$ is the dimension of the matrices involved. This means that $\text{rank}(B) = 0$ or $\text{rank}(B) = 1$.

It's clear that $\text{rank}(B) = 0$ if and only if $B = 0$. But in this case, we get:

$$0 = B = A-I \Rightarrow A = I,$$

which is a contradiction because $\text{rank}(A) = 2$. Then, we conclude that $$\text{rank}(B) = 1.$$

$\endgroup$
1
$\begingroup$

Notice that $B$ is not idempotent. Since $B=A-I$ and $A^2=A$ we have: $$BB=(A-I)(A-I)=A^2-2AI+I^2=A-2A+I=I-A=-B$$ $B$ is idempotent if $B=I-A$ but not if $B=A-I$. So the assumption that the rank of $B$ equals its trace is incorrect with the given definition of $B$.

$\endgroup$
1
$\begingroup$

BB = (A-I)(A-I) = AA - 2AI + II = A - 2A + I = I - A = -B, so B is not idempotent. In fact its trace is -1, and its rank is 1 (invoking, e.g., the result given in Seber, A Matrix Handbook for Statisticians, 8.79 [p. 171]).

$\endgroup$
0
$\begingroup$

We have $A^2-A=O$, which mean the eigenvalues of $A$ must be $0$ or $1$.

Using Sylvester inequality gives:

$$rank(A)+rank(A-I)\leqslant rank(A(A-I))+3$$

Thus $rank(A-I)\leqslant 1$

If $rank(A-I)=0$ then $A=I$, which is against $rank(A)=2$

So $rank(A-I)=1$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.